Kajian kimia zerumbon daripada Zingiber Zerumbet, Smith - Ahmad, Mohamad Syahrizal (2006)
Zerumbone, a sesquiterpenoid from the essential oil of Zingiber zerumbet, Smith has been isolated in 0.33% by recrystallization from n-hexane. Treatment of zerumbone with m-chloroperbenzoic acid (MCPBA), followed by methanolysis with N-bromosuccinimide (NBS) and methanol gave 2-hydroxy-3-methoxy-6,9-humuladien-8-one, while acetylation of 2-hydroxy-3-methoxy-6,9-humuladien-8-one afforded 2-acetoxy-3-methoxy-6,9-humuladien-8-one. Reaction of zerumbone with bromine (Br2) at -5ºC to -10ºC in carbon tetrachloride (CCl4) gave 6,7-dibromo-2,9-humuladien-8-one. Further treatment of 6,7-dibromo-2,9-humuladien-8-one with m-chloroperbenzoic acid (MCPBA) gave 6,7-dibromo-2,3-epoxy-9-humulen-8-one. Under nitrogen, zerumbone was reduced with lithium aluminium hydride (LiAlH4) at -5ºC to -10ºC to afford zerumbol. Acetylation and methylation of zerumbol gave 8-acetoxy-2,6,9-humulatriene and 8-methoxy-2,6,9-humulatriene, respectively. 2,3-Epoxy-6-ethoxy-9-humulen-8-one has been obtained by treating zerumbone with ethanol at 10°C to 15°C in the presence of boron trifluoride-etherate as catalyst, followed by epoxidation with m-chloroperbenzoic acid (MCPBA). 6,10-Dicyano-2-humulen-8-one was prepared by treatment of zerumbone with potassium cyanide at 15ºC to 20ºC in the presence of a-cyclodextrin. The deoxygenation of the zerumbone under the Clemmensen reduction, followed by Sharpless asymmetric dihydroxylation yielded (6S,7S)-6,7-dihydroxy-2,9-humuladien-8-one and (9S,10S)-9,10-dihydroxy-2,6-humuladien-8-one as the major and minor compounds respectively. Acetylation of (6S,7S)-6,7-dihydroxy-2,9-humuladien-8-one afforded (6S,7S)-6-acetoxy-7-hydroxy-2,9-humuladien-8-one, while further treatment of the acetoxy compound in the presence of 4-N,N-dimethylaminopyridine (DMAP) as catalyst gave (6S,7S)-6,7-diacetoxy-2,9-humuladien-8-one. (9S,10S)-9,10-Diacetoxy-2,6-humuladien-8-one has been obtained by acetylation of (9S,10S)-9,10-dihydroxy-2,6-humuladien-8-one in the presence of 4-N,N-dimethylaminopyridine (DMAP) as catalyst. Antibacterial screening showed that zerumbol gave a moderate inhibition to Bacillus subtilis with minimum concentration of 0.025 µg/µL and Pseudomonas aeruginosa with minimum concentration of 0.05 µg/µL. The results showed that 6,10-dicyano-2-humulen-8-one, (6S,7S)-6,7-dihydroxy-2,9-humuladien-8-one and (9S,10S)-9,10-dihydroxy-2,6-humuladien-8-one gave the highest antioxidant activity with the IC50 were 0.0171, 0.0227 and 0.0259 respectively.